2010
DOI: 10.1124/jpet.109.160226
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lysosomes in Limiting Drug Toxicity in Mice

Abstract: The distribution behavior of a drug within a cell is an important, yet often overlooked, variable in both activity and differential selectivity. In normal cells, drugs with weakly basic properties are known to be extensively compartmentalized in acidic organelles such as lysosomes via ion trapping. Several cancer cell lines have been shown to have defective acidification of endocytic organelles and therefore have a diminished capacity to sequester such lysosomotropic agents. In this study, we tested the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…In P-gp KO mice, pretreatment with tariquidar (32 mg/kg i.v.) decreased the uptake of (23), who demonstrated that lysosomal pH changes occur in mice when weak bases are administered chronically (i.e., for weeks) (23). However, we show that lysosomal competition between two weak bases can occur in vivo in an acute time frame, a finding that, to our knowledge, has not been demonstrated previously.…”
Section: Discussioncontrasting
confidence: 65%
“…In P-gp KO mice, pretreatment with tariquidar (32 mg/kg i.v.) decreased the uptake of (23), who demonstrated that lysosomal pH changes occur in mice when weak bases are administered chronically (i.e., for weeks) (23). However, we show that lysosomal competition between two weak bases can occur in vivo in an acute time frame, a finding that, to our knowledge, has not been demonstrated previously.…”
Section: Discussioncontrasting
confidence: 65%
“…4 Both these effects could hinder treatment. 4, 44, 45 Consequently, understanding the cellular distribution of chemotherapeutics, and how to manipulate this through combination treatments, is imperative for developing treatments against resistance.…”
Section: Discussionmentioning
confidence: 99%
“…26 Briefly, MDA-1986 cells were plated onto 8-chamber glass microscope slides and allowed to adhere overnight. Following a 24 h exposure to 10 µM imipramine or vehicle alone, growth media was replaced with phenol red-free growth media containing 1 mg/ml anionic 70,000 mol.…”
Section: Methodsmentioning
confidence: 99%